Acquired Vitelliform-Like Lesion in Uveitis: A case-series. (17th November 2022) - Maleki, Arash; Look-Why, Sydney; Asgari, Soheila; Manhapra, Ambika; Gomez, Sebastian; Foster, C. Stephen
ABSTRACT: Purpose: To study acquired vitelliform-like lesions (AVLL) and their diagnostic and prognostic values in uveitis. Patients and Methods: This was a retrospective case series. The clinical course, diagnostic value, and prognostic significance of AVLL were compared between uveitic patients with AVLL and uveitic patients without AVLL. Results: Twelve patients (21 eyes) with both uveitis and AVLL (study group) and thirteen patients (24 eyes) without AVLL (control group) were included in the study. Macular leakage ( p = .005), the presence of vasculitis ( p = .01), the presence of active choroiditis ( p = .01), and the presence of CME on OCT ( p = .008) were significantly higher in the AVLL group compared to the control group. Best-corrected visual acuity was significantly lower at presentation ( p < .001) and the last follow-up visit ( p = .014) in the AVLL group. Conclusion: The presence of acquired vitelliform-like lesion can have both a diagnostic (uveitis as a differential diagnosis) and prognostic value in patients with different types of uveitis.